EKSPLORASI PENGETAHUAN GURU IPA SMP TENTANG PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA : PENGUKURAN BERDASARKAN COMPLEX MULTIPLE-CHOICE SURVEY - Muhamad Arif Mahdiannur; Erman Erman; Martini Martini; Tutut Nurita; Laily Rosdiana (UIN Sumatera Utara Medan, 2022)
Changes in the national education curriculum and learning approaches in the Merdeka Curriculum become problems for teachers. In contrast, the key to successful curriculum implementation depends on the understanding and ability of teachers to translate and develop the curriculum itself. This study purposed to reveal science teachers’ knowledge and understanding on differentiated learning and the Merdeka Curriculum. This study involved sixty-five participants with a professional background as science teachers at the Lower Secondary School level. Small-scale surveys were conducted using complex multiple-choice item questions. This study reveals the average science teacher’s understanding of differentiated learning and the changes in science subjects in terms of content and process according to the Merdeka Curriculum only 37.85%. Furthermore, the findings show that current training had minimal impact on the science teachers’ preexisting knowledge. Therefore, according to the Merdeka Curriculum, the training pattern’s vital role must be concerned with developing teacher knowledge and understanding of changes in science subjects for the Lower Secondary School and the learning process. However, despite some limitations, we also think that the spaces for teachers’ curriculum agency patterns can be used to improve the science teachers’ knowledge and understanding on differentiated learning and the Merdeka Curriculum.